Coal-Mine Explosions Caused by Gas or Dust (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1915)
Discussion of the paper of HOWARD N. EAVENSON, presented at the Pittsburgh meeting, October, 1914, and printed in Bulletin No. 94, October,' 1914, pp. 2637 to 2660. GEORGE S. RICE, Pittsburgh, Pa.-I think it is very wise to point out the greater liability to explosions in certain parts of the year, if there be such difference, with the caution, however, that vigilance be not relaxed at other times. In comparing the figures for the United States with those of Europe, I think we should separate them as far as possible according to cause of origin and means of propagation. That is to say, it would appear to me that the majority of our explosions are due more directly to the ignition of coal dust directly from the flame of explosives, whereas, judging from my inquiries and observations in some of the mines of Europe, the majority of their explosions have been caused by the ignition of fire damp. Now, in the case of fire damp, I do not think that anybody has yet attempted or has been able to find any connection between the seasons and the issuance of methane into mines. One thing must be borne in mind, that if you get a strong explosion of fire damp, dust of a character that might not ignite readily by itself might assist in the extension of an explosion of fire damp through a considerable area in the mine, if not throughout the mine. While it is true we have many lesser explosions in this country attributable to fire damp, it would appear that the majority of all the mine explosions of the country, in considering the means of propagation beyond the locality of the origin, are due to coal dust; and it is the liability to coal-dust explosions that appears to be affected by seasonal changes. Hence the desirability of separating statistically (if it could be done by the inspectors) fire-damp explosions from coal-dust explosions, in order to obtain the true value of the seasonal effect. Nevertheless, in spite of the inclusion of fire-damp explosions with coal-dust explosions, the preponderance of the evidence, as indicated in Mr. Eavenson's figures for American mines, has shown that' in this country there were more explosions in the winter and spring months, when the mines are drier; that is, when the mines are apt to be drier. Whereas, according to the European figures that he has gathered, it seems to be very clearly demonstrated that in France, England, and Belgium, the time when explosions occur has no connection with any particular season. That, I think, is partly due to the point just mentioned, that a majority of their explosions have originated from fire damp. The European mining men have been more careful, generally speaking, with the use of explosives than we have, so that the cause of ignition from that source has been less. Only comparatively few of the mines in foreign